Determinants of peripapillary retinal nerve fiber layer thickness regarding ocular and systemic parameters: the MIPH Eye&Health Study - Schuster, Alexander K.; Fischer, Joachim E.; Voßmerbäumer, Urs (Graefe's archive for clinical and experimental ophthalmology, 2016)
BackgroundOptical coherence tomography (OCT) allows quantitative image analysis of retinal tissue in vivo. Peripapillary retinal nerve fiber layer (pRNFL) thickness is widely used for evaluation of retinal nerve fiber rarefaction in several optic neuropathies. This study evaluates associations of pRNFL thickness in healthy adult subjects in order to evaluate influencing factors.MethodsA cross-sectional study was performed in a working-age population. Only eyes without detectable ocular pathologies were included in the analysis. Among analyzed systemic cardiovascular parameters were age, gender, body-mass index, mean arterial blood pressure, HbA1c, high- and low-density-lipoproteins, and triglycerides. A comprehensive ophthalmological examination including refraction, tonometry, keratometry, and central corneal thickness measurmentwas performed. In addition, pRNFL thickness was imaged by spectral-domain OCT. Univariable and multivariable associations of pRNFL thickness in all four quadrants and on average with systemic and ocular parameters were calculated using a generalized estimating equation model.ResultsThree hundred and six subjects were included. pRNFL thickness measurements showed a significant association with spherical equivalent: pRNFL thickness decreased with increasing myopia in all quadrants (multivariable regression coefficients Beta: superior: 1.16, 95 % CI [0.62;1.71], p < 0.001; temporal: 0.87, [0.33;1.41], p = 0.001; inferior: 1.80, [1.18;2.42], p < 0.001; nasal: 2.60, [2.01;3.20], p < 0.001) and on average (1.51, [1.20;1.82], p < 0.001). A thicker central cornea thickness was related to lower pRNFL in the superior (−0.05, [−0.10; −0.01], p = 0.01), the inferior quadrant (−0.05, [−0.10;0.00], p = 0.03) and on average (−0.04, [−0.07; −0.01], p = 0.02). All other parameters were not associated.ConclusionOur findings highlight the importance of refraction when evaluating pRNFL thickness and its independence from other systemic parameters.
Gesehen am 17.07.2019